KAJIAN KERENTANAN BENCANA TSUNAMI DI PESISIR KABUPATEN KULON PROGO PROVINSI D. I. YOGYAKARTA - Widyawati, Ari; Handoyo, Gentur; Satriadi, Alfi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Coastal of Kulon Progo Regency is located in the southern coastal area of Java island that potentially vulnerable to tsunami disaster because of its geographical position that directly opposite the Indian Ocean and the meeting place of two tectonic plates, the Eurasian plate and the Indo- Australian plate which is tectonically very active and can be tsunami source. Identification of tsunami vulnerable areas in Kulon Progo Regency is a disaster mitigation step to minimize the negative impact of the tsunami. The purpose of this research is to map the vulnerability of the environment to the tsunami in Kulon Progo Regency coastal. There are five classes of tsunami vulnerabilities in Kulon Progo Regency coastal is the particularly vulnerable class 7.77 km2, 19.82 km2 vulnerable class, the class is quite vulnerable 33.98 km2, 51.38 km2 less vulnerable class, and the class is not vulnerable 31.19 km2 . The area included in very susceptible and vulnereable class in the village of Glagah, Jangkaran, Karang Sewu, Banaran, Sindutan, Palihan, Garongan, Pleret, and Bugel. The class are quit vulnerable, less vulnerable, and not vulnerable include around the village areas of reserarch in Galur, Panjatan, Wates, and Temon district.